Management of Fetal Growth Arrest in One of Dichorionic Twins: Three Cases and a Literature Review - Shoji Kaku; Fuminori Kimura; Takashi Murakami (Hindawi Limited, 2015)
Progressive fetal growth restriction (FGR) is often an indication for delivery. In dichorionic diamniotic (DD) twin pregnancy with growth restriction only affecting one fetus (selective fetal growth restriction: sFGR), the normal twin is also delivered prematurely. There is still not enough evidence about the optimal timing of delivery for DD twins with sFGR in relation to discordance and gestational age. We report three sets of DD twins with sFGR (almost complete growth arrest affecting one fetus for ≥2 weeks) before 30 weeks of gestation. The interval from growth arrest to delivery was 21-24 days and the discordance was 33.7-49.8%. A large-scale study showed no difference of overall mortality or the long-term outcome between immediate and delayed delivery for FGR, while many studies have identified a risk of developmental delay following delivery of the normal growth fetus before 32 weeks. Therefore, delivery of DD twins with sFGR should be delayed if the condition of the sFGR fetus permits in order to increase the gestational age of the normal growth fetus.